Multi-Watt Near-Infrared Phototherapy for the Treatment of Comorbid Depression: An Open-Label Single-Arm Study - Henderson, Theodore A.; Morries, Larry D. (Frontiers in Psychiatry, 2017)
Background The treatment of depression has been hampered by low efficacy of antidepressant medications and safety concerns with alternative modalities. Recent work demonstrated that multi-Watt transcranial near-infrared light therapy (NILT) can effectively treat traumatic brain injury (TBI). The current objective is to explore multi-Watt NILT efficacy in a proof-of-concept study as a treatment for depression. Methods Thirty-nine sequential patients treated for TBI between March 2013 and May 2017 provided depression self-assessment data and/or were administered the Hamilton depression rating scale. Each completed the Quick Inventory of Depression Symptomatology-Self Report (QIDS) before and after treatment. Patients received multi-Watt NILT using near-infrared lasers (810/980 nm at 8–15 W) applied to forehead and temporal regions bilaterally for 9–12 min to each area. Pre- and posttreatment scores were analyzed by paired t-tests. Results All met QIDS criteria for mild to severe depression and 69% had prior antidepressant trials. For 36 of the 39 patients, after 16.82 ± 6.26 treatments, QIDS scores indicated a robust response (decrease of QIDS total score by ≥50%). For 32 of 39 patients, posttreatment QIDS scores indicated a remission from depression (decrease of QIDS total score ≤5). Overall, the QIDS score fell from 14.10 ± 3.39 to 3.41 ± 3.30 SD (p = 6.29 × 10−19). With 12 or fewer treatments, QIDS score dropped from 14.83 ± 2.55 to 4.17 ± 3.93. Patients receiving ≥13 treatments showed a change in QIDS score from 13.67 ± 3.64 to 3.11 ± 3.14. Those (N = 15) who received the entire treatment course within ≤8 weeks (5.33 ± 1.72 weeks) showed a change in QIDS score from 13.86 ± 3.14 to 4.5 ± 3.94. Suicidal ideation resolved in all, but two patients. Patients remained in remission for up to 55 months after a single course of treatment. Conclusion This is the first report of high-powered NILT showing efficacy for depression. Multi-Watt NILT showed far greater efficacy and persistent benefit compared to low-power (<1 Watt) infrared light treatments. Patients saw benefit often within four treatments and resolution of depressive symptoms occurred within 4 weeks for some. These data raise an intriguing possibility—that multi-Watt NILT may be a safe, effective, and rapid treatment for depression comorbid with TBI and possibly primary major depression disorder. A double-blind, placebo controlled trial is warranted to verify these proof-of-concept data.